Performance of Lemon Grass (Cymbopogon citratus) as Vegetative Barrier in Eastern Ghats of Orissa - Dass, A.; Patnaik, U. S.; Sudhishri, S.; Paikaray, N. K.; Dwivedi, V. K. (Indian Forester, 2006)
A demonstrative field trial consisting of one common treatment of Lemon grass vegetative barrier and four treatments of four agricultural crops (Finger millet, Black gram, Pigeon pea and Black gram) was conducted under RBD replicated quarterly, at Research Farm of CSWCRTI, Research Centre, Sunabeda. Lemon grass was planted, double row staggered with inter row and intra row spacing of 30 cm across slope as vegetative barrier in integration with small trench-cum-bund at VI of 1.0 m at 4 per cent slope land. Till third year of planting, 74 per cent of clumps survived. Due to increase in clump size, inter-clump-space coverage increased from 16.65 per cent (initially) to 74.67 per cent after 2 years of planting. On an average, it conserved 41.41 t/ha/year of soil. This saved washing off of 236, 7.95, 0.54 and 7.05 kg/ha/year of organic carbon, available N, available P, and available K, respectively. Green biomass yield was 471.8 kg/ha, 1988 kg/ha and 2917.25 kg/ha during the year of planting, one-year after planting and two years after planting, respectively. The corresponding oil yield was estimated as 2.36, 9.94, and 14.59kg /ha, which can fetch additional gross returns of Rs. 826/-, Rs. 3,479/- and Rs. 5,105/-, respectively. Yield of all the crops within 1m distances from the barrier was negatively influenced. However at next 1 to 2m distances, a positive impact of Lemon grass barrier was observed on the economic yield of all the associated crops under trial.